The Influence of Tax Aggressiveness, Audit Committee, and Capital Structure on Corporate Social Responsibility Disclosure in Food and Beverage Companies Listed on the IDX - Ni Made Ari Puspita Dewi; Ni Putu Budiadnyani; Kadek Wulandari Laksmi P; Putu Pande R. Aprilyani Dewi (Jurnal Riset Perpajakan: Amnesty, 2025)
This study examines the influence of tax aggressiveness, audit committee, and capital structure on corporate social responsibility (CSR) disclosure in food and beverage companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. Using a purposive sampling technique, 192 firm-year observations were selected based on specific criteria. The study employed secondary data and was analyzed using the Statistical Product and Service Solutions (SPSS) software. The results of the multiple linear regression analysis show that tax aggressiveness and audit committee positively and significantly influence CSR disclosure. In contrast, capital structure has a negative and significant effect. These findings suggest that firms engaging in higher levels of tax aggressiveness may simultaneously enhance CSR disclosure, potentially as a reputational management strategy. Moreover, the presence of a stronger audit committee is associated with better CSR practices, indicating its critical role in governance and transparency. Conversely, firms with higher debt levels tend to disclose less CSR information, possibly due to financial constraints or strategic considerations. This study contributes to the literature by providing empirical evidence on the relationship between financial and governance factors and CSR practices within the Indonesian food and beverage industry context.